« La madame de la voiture ne veut rien comprendre » - François Perea (Communication)
Digital devices and interfaces are a big part of our environment today. Outside the home, automation is also taking over our cars. The author seeks to unpack some of the effects of technology in the automotive space by analyzing the linguistic behaviours induced by the devices themselves. After introducing the domotics of the passenger compartment and the approach taken to techno-linguistic devices, the author explores various aspects of discursive and interactional formatting based on a particular device before concluding with a discussion of the “mechanization” of language inasmuch as it can be assessed in the context observed.